2016
DOI: 10.1111/ajco.12653
|View full text |Cite
|
Sign up to set email alerts
|

Human epidermal growth factor receptor 2 status of gastric cancer patients in Asia: results from a large, multicountry study

Abstract: Aim Current estimates of the human epidermal growth factor receptor 2 (HER2)‐positivity rate in gastric cancer vary widely in the literature, and there are limited data from countries in Asia. The primary aim of this study was to conduct a clinical audit of laboratories across seven countries in Asia to determine the incidence of HER2‐positive gastric cancer in this region. Methods Pathologists were asked to collect data on patient gender, age, cancer site, specimen type, tumor spread, type and grade, HER2 tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Strikingly, the prevalence of ERBB2 gene amplification in Asian GC (21.4 vs. 11%) and CRC (11.1 vs. 5.5%) patients is higher than in non-Asian patient samples (Figure 3A). The former observation is consistent with a large study that identified HER2 overexpression, by IHC/ISH, in 9.7% of all Asian GC patients ( n = 5,301) and 18.1% when China was excluded from the analysis, suggesting regional differences in prevalence (25). In the case of primary CRC, however, another study reported an ERBB2 amplification/overexpression frequency of only 3.3% in an Asian patient cohort ( n = 4913).…”
Section: Discussionsupporting
confidence: 89%
“…Strikingly, the prevalence of ERBB2 gene amplification in Asian GC (21.4 vs. 11%) and CRC (11.1 vs. 5.5%) patients is higher than in non-Asian patient samples (Figure 3A). The former observation is consistent with a large study that identified HER2 overexpression, by IHC/ISH, in 9.7% of all Asian GC patients ( n = 5,301) and 18.1% when China was excluded from the analysis, suggesting regional differences in prevalence (25). In the case of primary CRC, however, another study reported an ERBB2 amplification/overexpression frequency of only 3.3% in an Asian patient cohort ( n = 4913).…”
Section: Discussionsupporting
confidence: 89%
“…In our investigation, the rate of HER2 overexpression determined by IHC alone was 6.7%, slightly lower than the previously reported values. HER2 overexpression is more frequent in advanced GC than in early GC 15 , 29 . This slight discrepancy can be explained by the fact that, unlike many other studies, our cohort only included patients with resectable stage II/III disease.…”
Section: Discussionmentioning
confidence: 96%
“…As per the studies available a wide range of HER2/ neu expression was observed in gastrointestinal adenocarcinomas. [6,7,8,9,10,11,12,13,14] In ToGA trial HER2 over expression of 3+ positivity was seen in 10.4% for resected samples. [2] For colorectal adenocarcinomas 3+ positivity on IHC was seen in 0.5 % cases.…”
Section: Discussionmentioning
confidence: 99%